2019
DOI: 10.1111/tid.13162
|View full text |Cite
|
Sign up to set email alerts
|

A case of immune reconstitution syndrome complicating progressive multifocal leukoencephalopathy after kidney transplant: Clinical, pathological, and radiographic features

Abstract: Progressive multifocal leukoencephalopathy (PML) is a life-threatening central nervous system (CNS) disorder, most commonly described in patients infected with the human immunodeficiency virus (HIV). Limited data exist on its natural history and treatment in solid organ transplant (SOT) recipients. A complication of PML is the immune reconstitution inflammatory syndrome (IRIS), which develops after T cell reconstitution and can have severe consequences when it occurs in the CNS. While well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…The basal ganglia, corpus callosum, and posterior fossa can be involved. Contrast enhancement has been reported in PML-IRIS among SOTRs [83].…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 87%
See 1 more Smart Citation
“…The basal ganglia, corpus callosum, and posterior fossa can be involved. Contrast enhancement has been reported in PML-IRIS among SOTRs [83].…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 87%
“…RIS is the mainstay for treatment. In kidney transplant recipients, complete elimination of immunosuppression may be considered as the SOTRs have the option of going back on dialysis [83]. Following favorable outcomes in a small group of nontransplant PML cases treated with Pembrolizumab [84], Medrano et al reported no improvement in outcomes in three SOTRs with PML who were treated the same regimen [85].…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 99%
“…In total, there have been 14 reported cases of PML post SOT or haematopoietic stem cell transplant (HSCT) in whom mirtazapine was used as adjunctive therapy and which are summarised in table 2 13 15–25. The reported time post-transplantation ranged from a few months to almost 20 years post-transplantation, with a mortality rate of 42.8% and reported survival of 10.7 months.…”
Section: Discussionmentioning
confidence: 99%
“…Hematologic malignancies are the most common risk factors associated with PML [31]. The management consists of the reduction of immunosuppression and, in people living with HIV infection, initiation of antiretroviral therapy (ART) has an improvement in their outcome [1,32]. The Swiss cohort reported three cases with late presentation (range 15–28 months), tapering of immunosuppression was done, and one had acute rejection and graft loss and ultimately died [3 ▪▪ ].…”
Section: Viral Central Nervous System Infectionsmentioning
confidence: 99%